M K Land Holdings Berhad: analysis of performance from 2005 to 2009 - Mohd Sharif, Nur Aziela (2010)
The collapse of the house price bubble led to the financial crisis that started in 2007. The crisis attacks most of countries around the world and the banking system. Performance of firm in every sector are said to be affected by the crisis. The previous literature describes that the construction sector was the most affected one. This study was done to evaluate the performance of M K Land Holdings Berhad, claimed as one of the largest construction firm in Malaysia. The findings show there is a gap between the previous theories with the actual performance of the firm.